Algorithm of Calculations of Helix-Coil Transition Parameters in Heteropolymeric Biopolymers on the Bases of Generalized Model of Polypeptide Chain - A. V. Asatryan
Algorithm of calculations of free energy, helicity degree and other parameters of helix-coil transition theory in the model of heterogen biopolymers with binary heterogeneity has been built. The theory is based on Generalized Model of Polypeptide Chain (GMPC). In the basics of algorithm is laying direct calculation of free energy with the help of random product of transfer matrices of homopolymeric GMPCs.
Keywords: Physics; Materials science; Cross-Disciplinary